The myth of the French bourgeoisie : an essay on the social imaginary, 1750-1850 - Maza, Sarah C., 1953- (Harvard University Press, 2003)
"In this new approach to an old question, Sarah Maza focuses on the crucial period before, during, and after the French Revolution, and offers a provocative answer: the French bourgeoisie has never existed. Drawing on political and economic theory and history, personal and polemical writings, and works of fiction, Maza argues that no group ever identified itself as bourgeois and that the bourgeoisie was never the social norm. In fact, it functioned as a critical counter-norm, an imagined and threatening embodiment of materialism, self-interest, commercialism, and mass culture, which defined all that the French rejected." "A challenge to conventional wisdom about modern French history, this book poses broader questions about the role of anti-bourgeois sentiment in French culture by suggesting parallels between the figures of the bourgeois, the Jew, and the American in the French social imaginary. It is a brilliant and timely foray into our beliefs and fantasies about the social world - their sources in theory, rhetoric, advertising, and mass fictions - and how we define a social class."--Jacket